Materials Engineering of Violin Soundboards by Stradivari and Guarneri. (27th June 2021) - Su, Cheng‐Kuan; Chen, Szu‐Yu; Chung, Jen‐Hsuan; Li, Guo‐Chian; Brandmair, Brigitte; Huthwelker, Thomas; Fulton, John L.; Borca, Camelia N.; Huang, Shing‐Jong; Nagyvary, Joseph; Tseng, Hsiao‐Han; Chang, Chih‐Hui; et al.
Abstract: We investigated the material properties of Cremonese soundboards using a wide range of spectroscopic, microscopic, and chemical techniques. We found similar types of spruce in Cremonese soundboards as in modern instruments, but Cremonese spruces exhibit unnatural elemental compositions and oxidation patterns that suggest artificial manipulation. Combining analytical data and historical information, we may deduce the minerals being added and their potential functions—borax and metal sulfates for fungal suppression, table salt for moisture control, alum for molecular crosslinking, and potash or quicklime for alkaline treatment. The overall purpose may have been wood preservation or acoustic tuning. Hemicellulose fragmentation and altered cellulose nanostructures are observed in heavily treated Stradivari specimens, which show diminished second‐harmonic generation signals. Guarneri's practice of crosslinking wood fibers via aluminum coordination may also affect mechanical and acoustic properties. Our data suggest that old masters undertook materials engineering experiments to produce soundboards with unique properties. Abstract : ICP‐MS is used to identify the unique mineral recipe used by Antonio Stradivari to treat his spruce wood, the material for the violin top plate. Chemical manipulation led to hemicellulose fragmentation and cellulose rearrangement. Incorporating engineered wood may contribute to the unique tonal qualities of these acclaimed instruments.